Addition of phenylisocyanate to 3, 5-diphenyl-1, 2-dithiolium-4-olate gives a thioketone. Issue 14 (5th April 2017) - Probert, Michael R.; Ramsden, Christopher A.; Stanforth, Stephen P.
Graphical abstract: Highlights: The reaction of phenylisocyanate with a mesoionic heterocycle produces a novel thioketone. The structures of products from similar reactions to that above have been either corrected or confirmed. X-ray crystallography and spectral data confirm the thioketone structure. Abstract: The Type B mesoionic heterocycle, 3, 5-diphenyl-1, 2-dithiolium-4-olate, reacts with phenylisocyanate producing a thioketone derivative rather than a pseudo-semi-conjugated heterocyclic mesomeric betaine. The structure of the thioketone product was confirmed by an X-ray crystallographic investigation.